THE CORRELATION OF ARM MUSCLE STRENGTH, GRIP STRENGTH, AND BODY FLEXIBILITY TO THE RESULTS OF LONG DISTANCE SHOTS ON WOODBALL - aditama, farid; Sugiharto, Sugiharto; Kusuma, Donny Wira Yudha (Journal of Physical Education and Sports, 2020)
This research aims to analyse and examine the correlation between arm muscle strength, grip strength, and body flexibility to the results of long distance shots on woodball. This research applied a correlational design with variables of arm muscle strength, grip strength, and body flexibility to the results of long distance shots on woodball. The samples of this research were 25 Central Java woodball athletes using a pull and push instrument dynamometer, handgrip dynamometer, sit and reach dynamometer and long distance shots test. The results of this research are the arm muscle strength gave an effect to the results of long distance shots by 13.18%. The grip strength gave an effect to the results of long distance shots by 9.42%. The body flexibility had an effect to the results of long distance shots by 7.78%. The arm muscle strength and the grip strength together had an effect to the results of long-distance shots by 24.50%. The arm muscle strength and the flexibility together gave an effect to the results of long-distance shots by 17.14%. The grip strength and the body flexibility together had an effect to the result of long distance shots by 13.63%. The arm muscle strength, the grip strength, and the togok flexibility together gave an effect to the results of long distance shots by 27.60%.